The philosophy of carbon: meso-entropy materials. (8th December 2020) - Feng, Boxu; Zhuang, Xiaodong
Abstract : The meso-entropy concept is proposed to re-understand the material world and to develop new carbon-rich materials. Abstract : In the past decades, the materials field has been developing widely and at a high speed, especially for carbon materials. The most popular carbon-rich materials include fullerenes, carbon nanotubes, graphene, graphite, diamond, and polycyclic aromatic hydrocarbons. Although studies appear to be exhaustive, the relationship between these materials remains unclear. Even for one of carbon-rich materials, the understanding at a chemistry level is still at the stage of hybridization difference. In this article, we propose a new method, the meso-entropy concept, to re-understand carbon materials and forecast new carbon-rich materials with new properties.